The Discounted Face of the Pornographic Other - Hoy, Andrew (Lumen et Vita, 2017)
French phenomenologist, Emmanuel Levinas, responds in Ethics and Infinity that, “[T]he relation to the face is straightaway ethical. The face is what one cannot kill, or at least it is that whose meaning consists in saying: ‘thou shalt not kill.’” For Levinas, it is the face of the Other which issues a cry that “I” become responsible for her. The face is signification, pointing to the transcendent and saturating mystery of the Other, yet is beyond the reduction of visual perception. It is the objective of this paper to apply Levinasian thought, the ethical response to the face of the Other, to the injustice associated with the production and commodification of pornographic images and videos. As the abuse of pornographic materials is an injustice, a failed response to the cry of the Other, it begs the question, “Does the pornographic Other even possess a face?” Subliminal as it may seem, this question is nonetheless essential to address in the consideration of pornographic injustice. This paper argues that in the case of the abuse and exploitation of the Other within the pornographic industry, the pornographic Other possesses a face which issues a cry to recognize the inviolable mystery of the Other and to become responsible for him or her. Pornography, by its very nature, discounts the face of the Other, not rendering the face unknowable, but never giving the face a chance to be known. From the beginning of the abuse, the pornographic viewer reduces that which cannot be reduced, the face, to an object for use, a direct violation of the ethical cry of the Other.